Prevention of Corrupt Behavior with the Maqashid Syariah Approach - Dede Rosyada; Madian Muchlis; Popi Puadah; Ira Silviana Suseno (Eduvest - Journal of Universal Studies, 2025)
This study aims to test the influence of religiosity, independence, professionalism, family resilience and remuneration as factors that affect corrupt behavior both partially and simultaneously so that efforts to prevent corrupt behavior through the Sharia Maqashid approach are obtained. The study used quantitative method, the population in this study is all employees in one agency that handles disasters. The sample size used was 269 respondents. The sampling technique used is Krijie Morgen. Based on the results of the study, it can be concluded that: (1) There is a significant influence partially or simultaneously between religiosity, independence, professionalism, family resilience and remuneration on corrupt behavior; (2) The application of "TANGGUH" values as an effort to prevent corrupt behavior through the Sharia Maqashid approach is another alternative to the efforts to prevent corrupt behavior that has existed so far. This research is expected to be useful from a theoretical and practical perspective. One of the benefits of the theory is to increase the insight of academics related to the influence of religiosity, independence, professionalism, family resilience and remuneration on corrupt behavior, while from the practical side, it is to provide advice to agencies in improving more reliable corruption prevention efforts through the internalization of the value of anti-corrupt behavior, namely "TANGGUH" (Resilient in religiosity, Resilient in Remuneration, Resilient in Independence,  Resilient in Professionalism and Resilient in Family Resiliency).